O controle judicial da gestão municipal do meio ambiente - Brandelli, Ailor Carlos (My University, 2014)
The recognition of the ambient good and its realization for the state beings demonstrate the necessity of if providing mechanisms with preventive and corrective performance in the preservation of the environment, as estimated for preservation of the proper humanity. Some mechanisms of procedural matrix are ranks the disposal of the citizen to control, to fiscalize and to demand the adoption of measures of preservation in face of the finitude of the existing environmental resources. In this aspect, the participation of the population in the fiscalization and the control of the management politics of the environment is measured to healthy for the preservation of the ambient good. However, impediments of procedural order, allies to the fact of that Brazil presents cultural contexts, social and economic with great disparity, if demonstrate as obstacles in effective the ambient and same preservation in the adoption of necessary public politics to the maintenance and preservation of the ambient good. It appears thus the necessity of if providing the institutions with State with a new model with management with the environmental resources, in special the cities, where they occur most of the administrative cases of ambient licensing, as well as, a new reading of the process that starts to manage diffuse and transindividual rights in this current model of performance in the ambient preservation.
O reconhecimento do bem ambiental e sua efetivação pelos entes estatais demonstra a necessidade de se prover mecanismos de atuação preventiva e corretiva na preservação do meio ambiente, como pressuposto para preservação da própria humanidade. Vários mecanismos de cunho processual são postos à disposição do cidadão para controlar, fiscalizar e exigir a adoção de medidas de preservação em face da finitude dos recursos ambientais existentes. Nesse aspecto, a participação da população na fiscalização e no controle da gestão política do meio ambiente é medida salutar para a preservação do bem ambiental. Entretanto, entraves de ordem processual, aliados ao fato de que o Brasil apresenta contextos culturais, sociais e econômicos com grande disparidade, se demonstram como óbices na efetiva preservação ambiental e mesmo na adoção de políticas públicas necessárias à manutenção e preservação do bem ambiental. Surge assim a necessidade de se prover as instituições de Estado de um novo modelo de gestão dos recursos ambientais, em especial os municípios, onde ocorrem a maior parte das ações administrativas de licenciamento ambiental, bem como, uma nova leitura do processo que passa a gerir direitos difusos e transindividuais nesse atual modelo de atuação na preservação ambiental.
Keywords: Direito; Gestão ambiental; Política pública; Jurisdição; Direito ambiental; Meio ambiente - Política governamental; Controle da poluição; Ambient management; Public politics; Jurisdiction; Jurisdiction; Environment - Government policy; Pollution control industry